Vegetation Scenarios Of Artificially Planted Mangrove Species in Sundarbans as a tool to Mitigate Climate Change Issues in Bangladesh - Siddqui, Asm Helal; Islam, MD. Akramul (Indian Forester, 2020)
Vegetation scenarios of artificially planted mangrove species such as Sundri (Heritiera fomes Buch.-Ham), Gewa (Excoecaria agallocha L), Goran (Ceriops decandra Griff. Ding Hou), Kankra (Bruguiera sexangula lour. Poiret), Kirpa (Lumnitzera racemosa Willd), Khaisi (Aegiceras corniculatum L. Blanco), Amoor (Amoora cucullata Roxb), Jhana (Rhizophora apeculata Lam) were studied in the Sundarbans which is the world’s largest contiguous mangrove forest from 2009 to 2018 in mesohaline and polyhaline zone in Bangladesh. The objectives of this research were to enrich vacant and poorly regenerated areas with a view to increase vegetation cover, biodiversity development, management and thus help to mitigate climate change through sustainable management of the ecosystem of the Sundarbans in this vulnerable delta. In the experimental plantation the average survival percentage of Sundri, Gewa, Goran, Kankra, Kirpa, Khaisi, Goran, Amoor, Jhana were 19%, 59%, 22%, 61%,75%, 54%, 8%, 26% in the polyhaline (> 18 ppt) zone and 22%, 75%, 9%, 47%,51%, 48%, 7%, 5% respectively in the mesohaline (5-18 ppt) zone. Average height (m) of the planted trees of eight species in the mesohaline zone were 3.18 m, 5.38 m, 4.54 m, 7.01 m, 3.71 m, 2.63 m, 1.53 m, 7.74 m and average DBH (cm) of the tree species measured 2.14 cm, 3.68 cm, 3.78 cm, 5.77 cm, 2.66 cm, and 7.5 cm respectively Besides average height (m) of eight species in the polyhaline zone were 2.84 m, 5.42 m, 4.47 m, 6.74 mâ€ž 3.74 m, 2.82 m, 1.04m, 7.48 m and average DBH of Sundri, Gewa, Goran, Kankra, Kirpa, Khaisi, Jhana (cm) were1.35 cm, 4.17 cm, 4.48 cm, 6.09 cm, 3.34 cm, and 8.04 cm respectively Therefore, it can be mentioned that Gewa, Goran and Khalshi in polyhaline zone showed better survival percentage and Jhana, Kirpa along with other species showed satisfactory growth performance in mesohaline and polyhaline zone simultaneously